2013
DOI: 10.1002/oa.2309
|View full text |Cite
|
Sign up to set email alerts
|

Geography and Economic Preferences as Cultural Markers in a Border Town: The Faunal Remains from Tel Beth‐Shemesh, Israel

Abstract: We present a zooarchaeological analysis of the faunal remains at Tel Beth-Shemesh, a site located in the Shephelah region of Israel, which has been dated to the Late Bronze Age and Iron Age I. The site, identified as the biblical city of Beth-Shemesh, was a Canaanite border town between Philistine and Israelite settlements and of great importance in our attempts to understand the social and cultural transformations that occurred in the southern Levant during those periods. This study contributes to a more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…showed that lack of pigs, or very low frequency of pigs, is a common feature of all Iron I sites outside of Philistia, sites that were inhabited by different cultural or ethnic groups. This continues traditional economic strategies that had been common in the Late Bronze Age (see also Tamar et al 2013). This pattern puts into question the ability to differentiate between Canaanites/ early Israelites and Philistines based on pig evidence alone, and suggests that significant consumption of pork can only serve to identify the population of the Philistine urban centers in the Iron I.…”
Section: The Philistinesmentioning
confidence: 90%
See 3 more Smart Citations
“…showed that lack of pigs, or very low frequency of pigs, is a common feature of all Iron I sites outside of Philistia, sites that were inhabited by different cultural or ethnic groups. This continues traditional economic strategies that had been common in the Late Bronze Age (see also Tamar et al 2013). This pattern puts into question the ability to differentiate between Canaanites/ early Israelites and Philistines based on pig evidence alone, and suggests that significant consumption of pork can only serve to identify the population of the Philistine urban centers in the Iron I.…”
Section: The Philistinesmentioning
confidence: 90%
“…The difference must therefore stem from dissimilar economic motivations at different sites, as was suggested by Lev-Tov (2000:208, 2010 regarding Tel Miqne/Ekron. Note that the livestock economy of neighboring Beth Shemesh and Tel Miqne/Ekron differs both in terms of pig frequencies (Bunimovitz and Lederman 2011;Tamar et al 2013) and relative frequencies of cattle and of sheep vs. goats (Sapir-Hen et al 2014). Thus, the economies of these sites may be viewed as complementary to each other (Sapir-Hen et al 2014).…”
Section: The Philistinesmentioning
confidence: 99%
See 2 more Smart Citations
“…At Lachish, we see the same mortality pattern as during the later MBA (Croft 2004a). Ovicaprid mortality at Tel Beth-Shemesh (Tamar et al 2013) and Timna (Lernau 1988) shows a focus on obtaining meat and secondary products. Tell Miqne/Ekron had sheep outnumbering goats, with a preference of slaughtering young and old ovicaprids.…”
Section: Synchronic Comparison Of Subsistence Patterns In the Shephelahmentioning
confidence: 99%